Disclosure of socio-environmental risk management: the case of Samarco Mineração - Schleiden Pinheiro Nascimento; Audiceia Lima Silva Andrade; Joelma Coelho Machado; Michele Monteiro Lirio Maria; Gabriel Moreira Campos (Revista Ambiente Contábil)
Purpose: To compare the changes in the disclosure of socio-environmental risk by Samarco, before and after the accident in Mariana (MG), which occurred in 2015.